PEDAGOGICAL FACTORS OF THE SOCIAL DEVELOPMENT OF YOUNG PEOPLE - Raxmatova Malika Rustamovna, (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
this article provides feedback on the pedagogical-psychological features of the social development and activity of young people.